WHAT IS THE TRUE CARBON FRACTION VALUE OF MANGROVE BIOMASS? - Rahman; Maryono; Sigiro, Oktavia Nurmawaty (Malaysian Journal of Science, 2023)
Carbon stock in mangrove stands is estimated through the biomass approach multiplied by the value of the mangrove carbon fraction. Many researchers use the value of 47% as the carbon fraction value for all mangrove species which should be based on the actual carbon content value. The research was conducted using the literature review method using a database ScienceDirect and Google Scholar until 2022. The search strategy was carried out using keywords: mangrove biomass, mangrove carbon stock, organic carbon of mangrove, carbon fraction of mangrove biomass, and chemical composition of mangrove biomass. The results showed that the value of the carbon fraction with the approach of organic carbon content was 46.4% and lower than the value of the carbon fraction with the approach of compounds making up mangrove biomass, which was 46.82%. This value was contributed by carbohydrates at 26.20%, amino acids 2.97%, tannins 3.22%, lignins 3.38%, fatty acids 7.69%, triterpenoids 3.17%, and n-alkanes 0.19. %. The estimation of mangrove carbon stock in forests with homogeneous species can use the value of carbon fraction in each mangrove species, namely 46.3% for B. gymnorrhiza, 45.9% for R. apiculata, and 47.1% for S. alba. Meanwhile , a carbon fraction value of 46.82% can be used for all true mangrove species to estimate the carbon stock in forests with heterogeneous mangrove species.